Effect of Simvastatin on Hepatic Venous Portal Gradient for Maintenance of Lipid Profile of Liver Cirrhosis patients - Bilal Rafique Malik, Umair Asghar, Rehan Anwar, Syed Mehmood-Ul-Hassan, Muhammad Wasim Salim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Liver cirrhosis has an essential influence on the lipid profile. Statins have well-known beneficial cardiovascular effects reducing cardiovascular events and mortality. Aim: To compare the change in hepatic venous portal gradient with or without simvastatin for maintenance of lipid profile of liver cirrhosis patients Methods: This Randomized controlled trial was done at Department of Medicine, South medical ward, Mayo hospital, Lahore from October 2021 to March 2022.patients were randomly divided in two groups. In group A, patients were given simvastatin with standard treatment. In group B, patients were given standard treatment only. Before and after 1 month of treatment, lipid profile and HVPG level were assessed again. The change in HVPG and lipid profile was calculated. Data was entered and analyzed in SPSS version 25. Results: The mean age of patients received simvastatin was 55.26 ± 13.24 years and mean age of patients in control was 53.74 ± 16.88 years. In simvastatin group, there were 82 (54.7%) males and 68(45.3%) females. In control group, there were 93 (62.0%) males and 57(38%) females. With simvastatin, the mean HVPG level was reduced from 20.11± 6.21mg/dl to 15.42±4.71 mg/dl after a month (mean change = 4.69 ± 1.50 mg/dl). While in control group, mean HVPG level was reduced from 19.28±7.61 mg/dl to 17.82± 6.52 mg/dl after a month (mean change = 1.46±1.09 mg/dl). The effect size was 23.3% with simvastatin while 7.6% without simvastatin for reduction of HVPG in cirrhotic patients. The difference was observed to be significant (p<0.05). Conclusion: Thus, addition of simvastatin is effective in controlling lipid profile of patients with liver cirrhosis. It also has beneficial role in improving condition of liver cirrhosis patients. Keywords: hepatic venous portal gradient, simvastatin, lipid profile, liver cirrhosis, LDL, HDL, total cholesterol, triglycerides